PDCA Cycle-Based Quality Management in Islamic Education and Its Alignment with Educational Management Standards - Khoirul Umam; Oki Dermawan; Aditia Fradito (Journal of Educational Management Research, 2026)
This study aims to analyze the implementation of quality management in Islamic educational management based on the Plan–Do–Check–Act (PDCA) cycle and its alignment with the Educational Management Standards stipulated in the Regulation of the Minister of Education, Culture, Research, and Technology Number 47 of 2023. This study employed a qualitative approach. Data were collected through interviews, observations, and document analysis involving school principals, teachers, and educational staff. The data were analyzed using the Miles and Huberman interactive model, while data credibility was ensured through source and technique triangulation. The findings indicate that quality management has been implemented systematically through the four stages of the PDCA cycle. The planning stage focused on educational program design, quality target setting, and religious program development. The implementation stage integrated academic learning, religious activities, character education, and an Islamic school culture. Evaluation was conducted through supervision, monitoring, and regular review meetings, while continuous improvement emphasized teacher professional development, program refinement, and educational innovation. These findings imply that integrating the PDCA cycle with national educational management standards provides a sustainable framework for strengthening institutional governance, improving educational quality, and supporting continuous quality assurance in Islamic educational institutions.